2021
DOI: 10.1016/j.atherosclerosis.2021.09.024
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cytokines and immune checkpoints in atherosclerosis with monoclonal antibodies

Abstract: Over the past fifteen years, treatments using monoclonal antibodies specifically targeting cytokines have been developed to treat chronic inflammatory diseases, including rheumatoid arthritis or psoriasis, both associated with increased cardiovascular risk. The cardiovascular impact of these therapies allows us to validate the clinical relevance of the knowledge acquired from experimental studies about the role of cytokines in atherosclerosis. Several clinical studies have confirmed the protective effects of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 152 publications
0
7
0
Order By: Relevance
“…Inhibition of CD40L has shown beneficial effects in many experimental models of auto-immune and chronic inflammatory diseases. Blocking CD40L/CD40 signaling has been shown to substantially reduce atherosclerotic burden, and improve inflammatory bowel disease, systemic lupus erythematosus, and rheumatoid arthritis in clinical trials and experimental mouse models [25,[46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of CD40L has shown beneficial effects in many experimental models of auto-immune and chronic inflammatory diseases. Blocking CD40L/CD40 signaling has been shown to substantially reduce atherosclerotic burden, and improve inflammatory bowel disease, systemic lupus erythematosus, and rheumatoid arthritis in clinical trials and experimental mouse models [25,[46][47][48][49][50].…”
Section: Discussionmentioning
confidence: 99%
“… 36 , 37 Over the past decade, monoclonal antibodies, against interleukin‐1β and interleukin‐17A, have been used to target pathogenesis of chronic inflammatory diseases, like psoriasis. 38 , 39 , 40 The CANTOS (Canakinumab Anti‐Inflammatory Thrombosis Outcomes Study) demonstrated evidence of targeting chronic inflammation to improve clinical outcomes, such as coronary plaque levels, in patients with atherosclerosis. 38 It has been demonstrated before that biologic therapy in severe psoriasis patients was associated with favorable modulation on coronary plaque phenotype measured by CCTA.…”
Section: Discussionmentioning
confidence: 99%
“… 38 , 39 , 40 The CANTOS (Canakinumab Anti‐Inflammatory Thrombosis Outcomes Study) demonstrated evidence of targeting chronic inflammation to improve clinical outcomes, such as coronary plaque levels, in patients with atherosclerosis. 38 It has been demonstrated before that biologic therapy in severe psoriasis patients was associated with favorable modulation on coronary plaque phenotype measured by CCTA. 4 With the current analyses, we sought to further understand the effect that elevated sLOX‐1 levels might have on coronary plaque progression in patients under specific psoriatic treatment.…”
Section: Discussionmentioning
confidence: 99%
“…While the molecular pathways of ICI-associated atherosclerosis beyond PD-1, PD-L1, and CTLA-4 are incompletely understood, approaches targeting novel co-stimulatory and co-inhibitory immune checkpoints, are currently under investigation ( Table 2 ). 58 , 59 , 60 …”
Section: Immune Checkpoints and The Pathophysiology Of Ici-related At...mentioning
confidence: 99%